The Effect Of Functıonal Open Bıte Treatment On Temporomandıbular Reactıon Force - Oktay Üner; Sevil Akkaya; Nilüfer Darendeliler; Seda Haydar (Galenos Yayinevi, 1997)
In this study, 10 patients with a chronological age of 10.40±1.12 years old who had a skeletal and dental open bite was studied on ten children of 10.40±1.12 years old by applying spring bite-block, The electromyographic (EMG) activities of anterior temporal and masseter muscles were recorded at the beginning and at the end of the treatment. A two-dimensional model was used to calculate the temporomandibular joint (TMJ) reaction force developed by muscle and bite forces. The cephalograms that had been taken at the beginning and at the end of the treatment were used in the formation of the model. A computer program were written for the computation of the TMJ reaction force. The study showed that the spring loaded posterior bite-block treatment has not altered the magnitude of the TMJ reaction force, but changed the direction of force to oblique for both incisor and molar bite forces. However, the variation in the direction of the TMJ reaction force was found significant only for the incisor bite force.